(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a scientific analysis of the impact of digital technologies on religious practices. In the 21st century, technologies such as the internet, social networks, mobile applications, and virtual reality have created new forms of religious life. Religious ceremonies (online worship, virtual hajj and pilgrimages), religious education (electronic Quran and Bible, online lessons, religious platforms) and the acceptance of religious values in the consciousness of society have undergone a significant transformation. The research methodology is based on the analysis of literature, a historical-sociological approach, comparison, empirical observation, and content analysis. The obtained results showed that religious traditions are not disappearing in the digital environment, but are taking on a new form in an adaptive way. Digital technologies ensure the openness of religious knowledge to the general public and expand the possibilities of global communication. At the same time, it creates problems such as the simplification, commercialization, and spread of misinterpretations of religious values. Analysis of research by foreign and domestic scientists shows that the rational use of digital technologies is important for the preservation of religious values and maintaining their relevance in modern society.